Ethics briefings - Davies, Martin (Journal of medical ethics, 2012)
In a recent high profile case1 the Court of Protection authorised the forcible-feeding of a seriously anorexic former medical student with a critically low body mass index (BMI). Without urgent medical treatment, the woman, referred to only as ‘E’, will die. Following four episodes of treatment in specialist eating disorder units and one in an alcohol treatment unit, E, her parents and the professionals involved in her care concluded that all available treatment options had been exhausted. She was transferred to a community hospital for palliative care and put on an ‘end of life’ care pathway. At a late stage her local authority sought court-review of her treatment. The Court of Protection held both that E lacked capacity with regard to her food refusal and that, if it were necessary, forcible-feeding would be in her best interests and therefore lawful. Although the law relating to the treatment of severely anorexic patients is well established, certain features of this case make it more challenging and arguably more controversial. In assessing E's best interests under the Mental Capacity Act, Mr Justice Jackson undertook a ‘balancing exercise.’ In favour of permitting E to remain on a palliative care pathway he placed the following factors: It reflects her wishes It respects her autonomy It spares her the risks associated with treatment It avoids the harrowing aspects of treatment It allows her to die with dignity and close to home Treatment has limited prospects of success E's parents and clinicians are at best sceptical about a positive outcome In favour of forcible feeding he placed the following: Without treatment she will die Without treatment she will lose the chance to recover and lead a relatively normal life There is medical opinion that she is treatable with some prospect of success The longer she lives, …